Peningkatan Kinerja Guru Dalam Memanfaatkan Aplikasi Sistem Informasi Harapan Bangsa (Si Haba) Sebagai Sumber Belajar - Faisal, Faisal (ISTIFHAM, 2023)
This study aims to determine the improvement of teacher performance in utilizing the Harapan Bangsa Information System application (Si Haba) as a learning resource through workshops at MTsS Harapan Bangsa West Aceh Regency in 2022. The subjects in this study were all MTsS Harapan Bangsa teachers of West Aceh Regency, totaling 38 people, consisting of 7 civil servant teachers and 31 non-civil servant teachers. The data collection technique used is observation. This research is carried out in two cycles: planning, implementation, observation, and reflection. The data analysis technique used is percentage descriptive. The results showed increased teacher performance in applying the Si Haba as a learning resource through workshops at MTsS Harapan Bangsa West Aceh Regency. This can be seen from the results of pre-action: teacher performance obtained an average score of 60.1 in the pretty good category, in the first cycle got an average score of 74.9 in the good category, and in the second cycle obtained an average score of 80.7 in the very good category. This proves the hypnotic statement stating that teacher performance in utilizing the Harapan Bangsa Information System (Si Haba) application as a learning resource can be improved through workshops at MTsS Harapan Bangsa West Aceh Regency in 2022, proven.